Authority and Attribution in the Sternhold and Hopkins Psalter - Rush, Rebecca M. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
This essay addresses the vexed question of the genre of the Sternhold and Hopkins psalter by considering the framing of the psalms in the early editions printed in England and on the continent. It is undeniable that all of the producers of the Sternhold and Hopkins psalter were committed to the dissemination of Scripture in the vernacular and that many were concerned with approximating the hebraica veritas. But comparing the title pages, prefaces, and marginal notes included in the sixteenth-century versions of the psalter with those of contemporary prose translations reveals that the editors of the psalter distinguished the metrical psalms from prose translations by carefully marking them as the poetic products of particular authors. In calling on the names and titles of the versifiers as sources of the volume’s authority, the editors of the Sternhold and Hopkins psalter forged an understanding of poetic authorship that would prove influential not only for later psalm translators but for English poets more generally. Indeed, this essay makes the case that the practices of authorial attribution employed in the psalters may have directly influenced the presentation of more celebrated verse anthologies like Tottel’s Songes and Sonettes.